Capsule - Novaes, Diego Pires de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This report presents the development of a vehicle designed for the national competition Volkswagen Design Talent 2015 in the category Shape Design (Exterior Design), in the period from June to December. The competition is held annually and it has been an innovative selection process since 1998, aimed to design students. It centralized to reveal new talents and select new trainees for the Company's Design area in Brazil. I took part in this selection process, the theme for its 17th edition was Cuts from Brazil. It challenged the development of a means of transportation for the year 2025 that would be is able to face the paths and supply the many different brazilian needs. This report presents the creation steps of the vehicle proposal process ranging from understanding the briefing presented, to the concept generation, tracing the brand's DNA for the year 2025 until obtains the best visual results. During the first and third (and last) selection periods the original proposal has evolved dramatically. The result was presented at the Volkswagen Design Center Brazil, Anchieta plant in São Bernardo do Campo (SP). The Project was selected among the 10(ten) finalists of the 17th contest edition. The defense of this concept car will be shown chronologically and entirely with visual language where with designers communicate day-by-day

Desenvolvimento do projeto de um veículo para o concurso nacional Volkswagen Talento Design 2015 na categoria Shape Design (Design de Exterior), no período compreendido entre os meses de junho a dezembro do respectivo ano. O concurso é um processo seletivo anual, realizado desde 1998, voltado a estudantes de design. Tem como objetivo revelar novos talentos e selecionar novos estagiários para a área de Design da empresa no Brasil. Participei desse processo seletivo, cujo tema em sua 17a edição foi Recortes do Brasil. Propõe como desafio o desenvolvimento de um meio de transporte para o ano de 2025, que possa enfrentar os caminhos e atender as diversas necessidades do Brasil. Este relatório apresenta as etapas do processo de criação da proposta de veículo, que vão desde o entendimento do briefing apresentado, a geração do conceito, a adaptação do projeto à identidade visual/ DNA da marca, traçar o DNA da marca para o ano 2025 até o melhor resultado visual final obtido. Durante esse período entre a primeira e última fase de seleção a proposta original evoluiu radicalmente. O resultado foi apresentado no Volkswagen Design Center Brasil, na fábrica Anchieta, em São Bernardo do Campo (SP). O projeto foi selecionado entre os 10 Finalistas da 17a edição do concurso. A defesa deste concept car será mostrada de forma cronológica e inteiramente visual, linguagem com a qual o designer se comunica no seu cotidiano
Keywords: Automoveis; Concursos; Desenho industrial; Veiculos; Contests